Kult adoracji eucharystycznej źródłem autentycznych chrześcijańskich postaw moralnych - Kwiatkowski, Dariusz (Teologia i Moralność, 2018)
The next most popular form of Eucharist, aside from Holy Mass, is the adoration of The Highest Sacrament. The article depicts the great force coming from the adoration and its infl uence on shaping Christian moral attitudes. A prayer in front of Christ, present in the Eucharist, is a necessity for building one’s sanctity and living with the rules of the Gospel. It also opens new ways of Christian lifestyle and shows proof of, hidden in The Highest Sacrament, Christ’s eucharistic love. This personal experience with the Saviour is a real spring of Christian moral attitudes, which are faith, hope and love. The adoration of The Highest Sacrament strengthens the believers on their way towards the eternity and allows them to anticipate it.